Using 5wh Competency Questions For Validating Information Retrieval From Al-quran: A Methodological Approach - Nazia Nishat; Rosalina Abdul Salam; Yusuf Mahbubul Islam; Zulkifly Mohd Zaki (Faculty of Science and Technology, Universiti Sain, 2025)
Malaysian Journal of Science Health & Technology, Volume 11 Issue 1 Page (132–141)